Insecticide dissipation from soil and plant surfaces in tropical horticulture of southern Benin, West Africa - Rosendahl, I.; Laabs, V.; Atcha-Ahowé, C.; James, B.; Amelung, Wulf (Royal Society of Chemistry, 2009)
In Sub-Saharan Africa, horticulture provides livelihood opportunities for millions of people, especiallyin urban and peri-urban areas. Although the vegetable agroecosystems are often characterized byintensive pesticide use, risks resulting therefrom are largely unknown under tropical horticulturalconditions. The objective of this study therefore was to study the fate of pesticides in two representativehorticultural soils (Acrisol and Arenosol) and plants (Solanum macrocarponL.) after field applicationand thus to gain first insight on environmental persistence and dispersion of typical insecticides used invegetable horticulture in Benin, West Africa. On plant surfaces, dissipation was rapid with half livesranging from 2 to 87 h (a-endosulfan <b-endosulfan < deltamethrin). Soil dissipation was considerablyslower than dissipation from plant surfaces with half-lives ranging from 3 (diazinon) to 74 d (totalendosulfan), but persistence of pesticides in soil was still reduced compared to temperate climates.Nevertheless, for deltamethrin and endosulfan, a tendency for mid-term accumulation in soil uponrepeated applications was observed. The soil and plant surface concentrations of the metaboliteendosulfan sulfate increased during the entire trial period, indicating that this compound is a potentiallong-term pollutant even in tropical environments.